2012
DOI: 10.1001/archophthalmol.2012.145
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Physicians, Patients, and Village Health Workers Toward Glaucoma and Diabetic Retinopathy in Rural China

Abstract: OBJECTIVE To understand the knowledge and attitudes of rural Chinese physicians, patients, and village health workers (VHWs) toward diabetic eye disease and glaucoma. METHODS Focus groups for each of the 3 stakeholders were conducted in 3 counties (9 groups). The focus groups were recorded, transcribed, and coded using specialized software. Responses to questions about barriers to compliance and interventions to remove these barriers were also ranked and scored. RESULTS Among 22 physicians, 23 patients, and 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
(51 reference statements)
2
23
0
Order By: Relevance
“…Multimedia educational interventions, when used alone, have been unsuccessful in increasing acceptance of low-cost comprehensive eye examinations 24 or cataract surgery 25 or in promoting purchase of children's spectacles. 26 Although a focus group study 27 indicated that patients in rural China may not be comfortable with direct cash payments to encourage medical compliance, Ma et al 28 have reported that the offer of free spectacles doubled spectacle wear at a later unannounced examination, which is consistent with improved adherence observed in the present study. It appears that the offer of free medical goods, such as medication and spectacles, may be particularly effective in this setting in changing behavior and gives the added advantage of direct clinical benefit to patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Multimedia educational interventions, when used alone, have been unsuccessful in increasing acceptance of low-cost comprehensive eye examinations 24 or cataract surgery 25 or in promoting purchase of children's spectacles. 26 Although a focus group study 27 indicated that patients in rural China may not be comfortable with direct cash payments to encourage medical compliance, Ma et al 28 have reported that the offer of free spectacles doubled spectacle wear at a later unannounced examination, which is consistent with improved adherence observed in the present study. It appears that the offer of free medical goods, such as medication and spectacles, may be particularly effective in this setting in changing behavior and gives the added advantage of direct clinical benefit to patients.…”
Section: Discussionsupporting
confidence: 83%
“…b Three patients were unavailable for follow-up at 2 weeks and 4 patients were unavailable for follow-up at 1 mo after surgery. The result of the current study, in which adherence was nearly doubled with an intervention costing less than US$25 per patient, may be compared with other reports [24][25][26][27][28] on interventions to enhance uptake of or adherence with eye care in rural China. Multimedia educational interventions, when used alone, have been unsuccessful in increasing acceptance of low-cost comprehensive eye examinations 24 or cataract surgery 25 or in promoting purchase of children's spectacles.…”
Section: Discussionmentioning
confidence: 79%
“…However, our finding that low income and lack of an accompanying person were important risk factors for failure to return to clinic as directed suggests that financial incentives to patients, family members and other potential escorts could also be of value, and might be combined with educational interventions. Financial incentives might include free medications or cell phone top-ups, as previous focus group studies have indicated that patients in rural China are uncomfortable with direct cash payments to encourage medical compliance 28. Shortening waiting times in the clinic might also decrease escorts' burden of time spent and wages lost.…”
Section: Discussionmentioning
confidence: 99%
“…The CREST programme aims to create a rural model of comprehensive eye care, including the specific goal of developing capacity to diagnose and treat DR, including DMO. From the outset, the project was designed to compare the accuracy and efficiency of two screening methods in the assessment of DR,12 trained rural ophthalmologists and non-medical graders using digital images.…”
Section: Methodsmentioning
confidence: 99%